Sistem Akuntansi Manajemen sebagai Pemediasi Pengaruh Gaya Kepemimpinan dan Desentralisasi terhadap Kinerja Manajerial (Studi pada Satuan - Rante, Andika; Djamhuri, Ali; Rosidi (Jurnal Aplikasi Manajemen, 2014)
The aim of this study was to examine whether Accounting System Management (MAS) be able to mediate between the effect of leadership styles and decentralization on managerial performances. The population is work unit heads of Jayapura City with samples were 39 respondents. The analysis that was used in this study is Path Analysis. The results show that leadership style and decentralization affect on managerial performance and ManagementAccounting System (MAS) can be mediating between the effect of leadership styles and decentralization on managerial performances.